Measurement and Determination of the Roles of Entities Responsible for Disseminating Banking Literacy: An Applied Study in a Sample of Iraqi Banks (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:           The research originates from a significant issue related to the banking sector in general, as the decline in the level of banking literacy creates a fertile ground for spreading rumors against banks. Additionally, customers' reluctance to adopt banking services contributes to an environment lacking trust between the bank and the customer. The research aimed to measure the roles of each entity responsible for promoting banking literacy. The hypotheses were substantiated, affirming that the bank plays a role in disseminating banking literacy to its customers, and customers play a role in accepting and acquiring banking literacy. Employing a descriptive-analytical approach, the study constructed a questionnaire distributed to 50 respondents, with 46 analyzable responses. The research revealed that customers play a crucial role in obtaining banking literacy, particularly based on their personality traits. Neglectful customers may not prioritize acquiring banking literacy, even if their transactions with the bank are substantial and continuous. On the other hand, diligent customers actively seek banking literacy, even with limited transactions with the bank. The research recommends that banks simplify methods for obtaining banking literacy and adopt a reinforcement strategy, continually advertising the nature of banking services and the rights and responsibilities of customers. Moreover, diversifying the methods of delivering this literacy to customers is emphasized